Penguasaan Kosakata Bahasa Mandarin Siswa Kelas X SMAS Celebes Global School Makassar - Tri Mega Utami; Ambo Dalle; Arini Junaeny (Universitas Negeri Makassar, 2022)
This study is a quantitative descriptive study that aims to determine the mastery of Chinese vocabulary and the factors that influence the mastery of Chinese vocabulary in class X SMAS Celebes School Makassar. The population in this study was class X SMAS Celebes School Makassar which amounted to 10 students. The sampling technique was carried out using total sampling, so the sample of this study was 10 students of class X SMAS Celebes School Makassar. The data of this study were obtained from a vocabulary mastery test, while to find out the factors that influence students' mastery of Chinese vocabulary, a questionnaire was used. Data analysis using percentage technique. The results showed that the student's mastery of Chinese vocabulary was in a good category (82.4%). From the results of the questionnaire data analysis obtained 1) Supporting factors, namely because of the interest of students who are interested in learning Mandarin, because of the encouragement of a good relationship between teachers and students, and supported by the use of interesting learning media. 2) The inhibiting factors based on student statements are; that Chinese vocabulary is difficult to learn, students only have Chinese books from school and students have never studied Mandarin other than at school. Keywords: Mastery, Vocabulary, Mandarin language.